2022
DOI: 10.1111/apa.16307
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid valve prolapse as an early predictor for severe phenotype in children with Marfan syndrome

Abstract: Marfan syndrome (MFS) is a multifaceted genetic disorder with a reported prevalence of 6.5 in every 100,000. 1 It involves many organ systems such as the cardiovascular and skeletal systems, the eye, skin, lung and dura. Onset of MFS manifestations is age-dependent and the phenotypes are highly variable. Safe predictors for severity of the disease are still missing. [2][3][4] Besides aortic root dilatation in MFS, other cardiac pathologies can be present in the atrioventricular valves. 5,6 Current literature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In a recent paediatric study of patients with Marfan’s disease, TVP occurred in 68% of the patients and correlated with mitral valve prolapse. 28 Nevertheless, an association between connective tissue disease and TVP is difficult to extrapolate to our cohort because of the significant difference in age, time of disease onset, and co-morbidities between the two cohorts.…”
Section: Discussionmentioning
confidence: 84%
“…In a recent paediatric study of patients with Marfan’s disease, TVP occurred in 68% of the patients and correlated with mitral valve prolapse. 28 Nevertheless, an association between connective tissue disease and TVP is difficult to extrapolate to our cohort because of the significant difference in age, time of disease onset, and co-morbidities between the two cohorts.…”
Section: Discussionmentioning
confidence: 84%
“…Also, at follow-up, aortic root dilatation and systemic manifestations were more present in the TVP group than the non-TVP group. Considering that TVP appears early in the disease course, the authors concluded that TVP should be routinely and regularly assessed in the echocardiography of MFS children as a possible predictor of clinical severity outcome (Stark et al, 2022) [51].…”
Section: Valves Tricuspid Valvementioning
confidence: 99%
“…Based on the exclusion of primary congenital anomalies of the TV apparatus, TVP was believed to be secondary to the rupture of chordae tendineae in our case. This lesion has been reported to be caused by ischemic etiologies, including hypoxemia, myocardial infarction, connective tissue diseases, thromboembolism, fibromyxomatous changes, and rhesus isoimmunization, as well as non-ischemic etiologies, such as infectious endocarditis, trauma, endomyocardial biopsy (26)(27)(28)(29)(30)(31). However, it is noteworthy that pressure overload of the RV can also cause rupture of the chordae or papillary muscles.…”
Section: Before Surgery After Surgerymentioning
confidence: 99%